Hidrovias no Brasil: Perspectiva histórica custos e institucionalidade - Fabiano Mezadre Pompermayer; Carlos Álvares da Silva Campos Neto; Jean Marlo Pepino de Paula (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– The waterway transportation is considered the most efficient. Moreover, Brazil has many rivers, besides the extensive coastline, appropriate to navigation. However, this mode of transport is not widely used in the country, especially inland. This study evaluates the possible causes for this. From a historical perspective, a waterway is characterized and its potential use in the country is evaluated, especially for the distribution of agricultural production. Costs of operation and deployment of a waterway are compared with a railroad. Despite these costs depend on the natural river navigability, the cost structure is favorable to the waterway, specially in rivers of low to medium course. Institutional analysis indicates that despite being the mode of transportation that gets less public investment, there are a greater number of public agents involved, with various plans and programs in progress, but without proper integration. Moreover, there is a lack of reliable information on the cost of investments needed, exacerbated by the fact that Technical, Economic and Environmental Feasibility Studies are still under development, impairing decision making on such investments. The review recommends that the implementation and operation of waterways should be transferred to the private sector through simple concessions, with toll collection, allowing expedite the necessary work and giving prospects for continuity of operations for carriers, since the maintenance of navigability on the waterways will not depend on public resources.
Keywords: H54; L98; L92; R42; R48; 330; waterway transportation; public investments